Lymphatic ascites following lymphadenectomy for gynecological tmalignancy. Issue 5 (1st September 2001) - Krishnan, C. S.; Grant, P. T.; Robertson, G.; Hacker, N. F.
Abstract : Seven patients seen between January 1995 and December 1998 developed symptomatic lymphatic ascites following either pelvic or para-aortic lymph node dissection. The incidence of symptomatic lymphatic ascites during this 4-year period was 2.7% (7 of 263 cases). The accumulation of ascites postoperatively was associated with a prolonged postoperative ileus, abdominal pain, and extended postoperative hospitalization. Once the condition was recognized, abdominal paracentesis resulted in rapid improvement of symptoms in two patients but repeated paracenteses were required for a further two patients who had significant complications as a result of these procedures. Two patients improved following spontaneous drainage of a large amount of ascites per vagina and did not require further intervention. The final patient settled with observation only. This condition can be difficult to recognize and is a potential cause of significant postoperative morbidity.